Homo- and Dikaryons of the Arbuscular Mycorrhizal Fungus Rhizophagus irregularis Differ in Life History Strategy - Serghi, Edward Umberto; Kokkoris, Vasilis; Cornell, Calvin; Dettman, Jeremy; Stefani, Franck; Corradi, Nicolas (Frontiers in Plant Science, 2021)
Arbuscular mycorrhizal fungi (AMF) are obligate plant symbionts that have the potential to improve crop yield. These multinucleate organisms are either “homokaryotic” or “dikaryotic”. In AMF dikaryons, thousands of nuclei originating from two parental strains coexist in the same cytoplasm. In other fungi, homokaryotic and dikaryotic strains show distinct life history traits (LHTs), such as variation in growth rates and fitness. However, how such traits compare between dikaryons and homokaryons of AMF is unknown. To address this, we measured 20 LHT of four dikaryons and five homokaryons of the model fungus Rhizophagus irregularis across root organ cultures of three host plants (carrot, chicory, and tobacco). Our analyses show that dikaryons have clearly distinct life history strategies (LHSs) compared to homokaryons. In particular, spores of homokaryons germinate faster and to a higher proportion than dikaryons, whereas dikaryons grow significantly faster and create a more complex hyphal network irrespective of host plant species. Our study links AMF nuclear status with key LHT with possible implications for mycorrhizal symbiotic functioning.